Impact of tricuspid valve regurgitation in surgical high-risk patients undergoing MitraClip implantation: results from the TRAMI registry - Kalbacher, Daniel; Bekeredjian, Raffi (EuroIntervention, 2017)
Aims: We sought to assess the impact of tricuspid regurgitation (TR) severity on patient outcome in a collective with relevant mitral regurgitation undergoing MitraClip implantation. Methods and results: From August 2010 to July 2013, 766 patients (age 75.3±8.5 years, 61% male, median EuroSCORE 24.3%±18.4) were prospectively enrolled in the TRAMI registry and stratified by echocardiography into no/mild, moderate and severe TR. Overall, the mean number of implanted MitraClips was higher in patients with severe TR but increasing TR severity was not associated with procedural success. In-hospital and one-year mortality as well as MACE and MACCE (death, myocardial infarction±stroke) rates were higher with increasing TR severity. Kaplan-Meier curves indicated a significant difference for mortality (p<0.0001), but not for rehospitalisation for heart failure. After multivariate Cox regression, severe TR proved to be a predictor for one-year mortality (HR 2.01, 95% CI: 1.25-3.26, p=0.004). Higher rates of severe bleeding were more frequent with increasing TR grades. Conclusions: In patients with MitraClip implantation, increasing TR severity is associated with adverse outcome, higher bleeding rates and decreased survival rates.